The increasing importance of Haemophilus influenzae in community-acquired pneumonia: results from a Danish cohort study. Issue 2 (1st February 2021) - Fally, Markus; Israelsen, Simone; Anhøj, Jacob; Benfield, Thomas; Tarp, Britta; Kolte, Lilian; Ravn, Pernille
Abstract: Background: Numerous studies have shown that the aetiology of community-acquired pneumonia (CAP) varies considerably among different healthcare settings. Because empiric therapies for CAP should cover the major pathogens, reports examining CAP aetiology are considered crucial, particularly in Nordic countries that still rely on penicillin G or V treatments for most patients with CAP. The primary objective of our study was to report CAP aetiology. Secondary objectives included the estimation of positivity rates for different tests and the odds of a positive test for various subgroups. Methods: In this cohort study, microbiological data were analysed for an overall cohort (variable degree of microbiological testing) and for a subgroup that was tested for both, bacteria, viruses and fungi, using routine methods (defined as extensive testing). Results: The overall cohort comprised 2, 264 patients, including 315 who were extensively tested. Bacterial and viral monoinfections were the most commonly identified infections. The dominant pathogen identified among extensively tested patients was Haemophilus influenzae (23.7%), followed by Streptococcus pneumoniae (20.6%). The tests with the highest positivity rates were sputum cultures (34.7%) and viral polymerase chain reaction (PCR, 24.4%). The odds of achieving a microbiological diagnosis increased significantly when extensive testing was performed compared with selective testing (OR 2.86, 95% CI 2.24–3.64). Conclusion: Our study indicated that H. influenzae is the dominant responsible pathogen for bacterial CAP in Denmark. Thus, we believe that the current treatment recommendations that encourage the use of penicillin G or V for the majority of patients with CAP need to be revised.